Ù‚Ø§Ø¹Ø¯Ø© Ø§Ù„Ø£ØµÙ„ Ø¨Ù‚Ø§Ø¡ Ù…Ø§ ÙƒØ§Ù† Ø¹Ù„Ù‰ Ù…Ø§ ÙƒØ§Ù† ÙˆØªØ·Ø¨ÙŠÙ‚Ù‡Ø§ ÙÙŠ Ø§Ù„ØµØ§Ø¦Ù… Ø§Ù„Ø°ÙŠ Ø£ÙØ·Ø± Ù‚Ø¨Ù„ ØºØ±ÙˆØ¨ Ø§Ù„Ø´Ù…Ø³ Ø®Ø·Ø£Ù‹: Ø¯Ø±Ø§Ø³Ø© Ù…Ù‚Ø§Ø±Ù†Ø© Ø¨ÙŠÙ† Ø§Ù„Ù…Ø°Ø§Ù‡Ø¨ Ø§Ù„Ø£Ø±Ø¨Ø¹Ø© ÙˆØ´ÙŠØ® Ø§Ù„Ø¥Ø³Ù„Ø§Ù… Ø§Ø¨Ù† ØªÙŠÙ…ÙŠØ© - Syandri, Syandri; Ikhsan, Muhammad; Hendri, Abi (Ø§Ù„Ø¨ØµÙŠØ±Ø©: Ù…Ø¬Ù„Ø© Ø§Ù„Ø¯Ø±Ø§Ø³Ø§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©, 2021)
This research discusses the law of the people who break the fast assuming the sun has set, then proved afterwards that the sun has not set by comparing the four schools and Shaykh al-IslÄm Ibn Taymiyyah, as well as how the implementation of the rule al-Aá¹£l BaqÄ' mÄ KÄn 'alÄ mÄ KÄn. This research aims to find out how the law of fasting according to the four schools, Shaykh Islam Ibn Taymiyyah in this matter, and how the above rules are implemented in this matter. The scientific method used in this study is inductive and deductive methods. The results showed that the law of fasting according to jumhÅ«r al-ulamÄâ€™ for people who break the fast assuming the sun has set, then it is clear afterwards that the sun has not set is the unvalid fast, and he is obliged to replace (qaá¸Äâ€™) it based on the proposition in their view. JumhÅ«r put this issue in the rule of al-aá¹£l baqÄ' mÄ kÄn 'alÄ mÄ kÄn. In contrast to Shaykh al-IslÄm Ibn Taimiyah who considers that his fasting is valid and unnecessary based on the proposition on which he handles it, and he does not include this problem in the rule of al-aá¹£l baqÄ' mÄ kÄn 'alÄ mÄ kÄn.